The first book of Kings with introduction and notes - Barnes, William Emery (Cambridge, UK Cambridge UP, 1911)
Includes bibliographical references and indexes.
Donated by Mrs F. Hunter.
Keywords: Bible. O.T. Kings, 1st -- commentaries